Prevalence of juvenile myoclonic epilepsy in people <30 years of age—A population‐based study in Norway. (16th November 2016) - Syvertsen, Marte; Hellum, Morten Kristoffer; Hansen, Gunnar; Edland, Astrid; Nakken, Karl Otto; Selmer, Kaja Kristine; Koht, Jeanette
Summary: Objective: Despite juvenile myoclonic epilepsy (JME) being considered one of the most common epilepsies, population‐based prevalence studies of JME are lacking. Our aim was to estimate the prevalence of JME in a Norwegian county, using updated diagnostic criteria. Methods: This was a cross‐sectional study, based on reviews of the medical records of all patients with a diagnosis of epilepsy at Drammen Hospital in the period 1999–2013. The study population consisted of 98, 152 people <30 years of age. Subjects diagnosed with JME, unspecified genetic generalized epilepsy, or absence epilepsy were identified. All of these patients were contacted and asked specifically about myoclonic jerks. Electroencephalography (EEG) recordings and medical records were reevaluated for those who confirmed myoclonic jerks. Information about seizure onset was obtained from the medical records, and annual frequency of new cases was estimated. Results: A total of 55 subjects fulfilled the diagnostic criteria for JME. The point prevalence was estimated at 5.6/10, 000. JME constituted 9.3% of all epilepsies in the age group we investigated. Of subjects diagnosed with either unspecified genetic generalized epilepsy or absence epilepsy, 21% and 12%, respectively, had JME. We identified 21 subjects with JME (38%) who had not been diagnosed previously. Six subjects (11%) had childhood absence epilepsy evolving into JME. Between 2009 and 2013, the average frequency of JME per 100, 000 people of all ages per year was estimated at 1.7. Significance: A substantial portion of people with JME seem to go undiagnosed, as was the case for more than one third of the subjects in this study. By investigating subjects diagnosed with unspecified genetic generalized epilepsy or absence epilepsy, we found a prevalence of JME that was considerably higher than previously reported. We conclude that JME may go undiagnosed due to the underrecognition of myoclonic jerks. To make a correct diagnosis, clinicians need to ask specifically about myoclonic jerks.